2019
DOI: 10.1101/749143
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Resurrection of ancestral effector caspases identifies novel networks for evolution of substrate specificity

Abstract: Apoptotic caspases evolved with metazoans more than 950 million years ago (MYA), and a series of gene duplications resulted in two subfamilies consisting of initiator and effector caspases. The effector caspase genes (caspases-3, -6, and -7) were subsequently fixed into the Chordata phylum more than 650 MYA when the gene for a common ancestor (CA) duplicated, and the three effector caspases have persisted throughout mammalian evolution. All caspases require an aspartate residue at the P1 position of substrates… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
2

Relationship

4
1

Authors

Journals

citations
Cited by 9 publications
(31 citation statements)
references
References 81 publications
2
29
0
Order By: Relevance
“…Reconstructions of ancestral effector caspases showed that the polar glutamate in the caspase-6 lineage is moved away from the S4 subsite by hydrogen bonding to a network of amino acids on helices-4 and -5, as described above (11). The interactions result in rotation of a hydrophobic group on active site loop 4 (L4), called GP9-V01, into the S4 subsite ( Figure 1C) (11). The charged network on helices 4 and 5, observed in caspase-6, is incomplete in caspases-3 and -7, and the hydrophobic GP9-V01 is substituted with glutamate in the DxxDases ( Figure 1D).…”
Section: Comparing Caspases From Human and Zebrafish Suggest Sites Thmentioning
confidence: 86%
See 3 more Smart Citations
“…Reconstructions of ancestral effector caspases showed that the polar glutamate in the caspase-6 lineage is moved away from the S4 subsite by hydrogen bonding to a network of amino acids on helices-4 and -5, as described above (11). The interactions result in rotation of a hydrophobic group on active site loop 4 (L4), called GP9-V01, into the S4 subsite ( Figure 1C) (11). The charged network on helices 4 and 5, observed in caspase-6, is incomplete in caspases-3 and -7, and the hydrophobic GP9-V01 is substituted with glutamate in the DxxDases ( Figure 1D).…”
Section: Comparing Caspases From Human and Zebrafish Suggest Sites Thmentioning
confidence: 86%
“…In contrast, CP162 is conserved in caspases-3 and -7 (DxxDases) as asparagine (Figure 1, panels B, D and Figure 2E). Reconstructions of ancestral effector caspases showed that the polar glutamate in the caspase-6 lineage is moved away from the S4 subsite by hydrogen bonding to a network of amino acids on helices-4 and -5, as described above (11). The interactions result in rotation of a hydrophobic group on active site loop 4 (L4), called GP9-V01, into the S4 subsite ( Figure 1C) (11).…”
Section: Comparing Caspases From Human and Zebrafish Suggest Sites Thmentioning
confidence: 89%
See 2 more Smart Citations
“…Enzyme activity was determined in a buffer of 150 m m Tris-HCl, pH 7.5, 50 m m NaCl, 10 m m DTT, 1% sucrose, 0.1% CHAPS (assay buffer) at 25°C, as described previously ( 57 , 58 ). The total reaction volume was 200 μl, and the final enzyme concentration was 10 n m .…”
Section: Methodsmentioning
confidence: 99%